Systems Biology of Cancer: A Challenging Expedition for Clinical and Quantitative Biologists - Korsunsky, Ilya; McGovern, Kathleen; LaGatta, Tom; Olde Loohuis, Loes; Grosso-Applewhite, Terri; Griffeth, Nancy; Mishra, Bud (Frontiers in Bioengineering and Biotechnology, 2014)
A systems-biology approach to complex disease (such as cancer) is now complementing traditional experience-based approaches, which have typically been invasive and expensive. The rapid progress in biomedical knowledge is enabling the targeting of disease with therapies that are precise, proactive, preventive and personalized. In this paper, we summarize and classify models of systems biology and model-checking tools which have been used to great success in computational biology and related fields. We demonstrate how these models and tools have been used to study some of the twelve biochemical pathways implicated in but not unique to pancreatic cancer, and conclude that the resulting mechanistic models will need to be further enhanced by various abstraction techniques to interpret phenomenological models of cancer progression.